2015
DOI: 10.1016/j.econlet.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Does money matter in the euro area? Evidence from a new Divisia index

Abstract: • Money has virtually disappeared from standard monetary models:• Empirical failures: estimated money demand functions found to be unstable; money proved to be less effective in predicting economic outcomes;• Policy shifts: central banks focus on interest rates;• Theory: development of theories suggesting that money is redundant.• Measurement problem?• Standard (simple sum) monetary aggregates were used, but:• E.g. cash and bank debt securities quite different, yet simple sum money aggregation assumes they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Puah et al (2006) found that the long-run neutrality of money hypothesis does not hold in Malaysia, and monetary expansion measured using Divisia money appears to produce a positive effect on real output in the long run. Darvas (2014) also reveals that Divisia monetary aggregates are able to affect output, prices and interest rates in the Euro area.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Puah et al (2006) found that the long-run neutrality of money hypothesis does not hold in Malaysia, and monetary expansion measured using Divisia money appears to produce a positive effect on real output in the long run. Darvas (2014) also reveals that Divisia monetary aggregates are able to affect output, prices and interest rates in the Euro area.…”
Section: Literature Reviewmentioning
confidence: 96%
“…While Darvas (2015) provides a Divisia aggregate under the assumption of homogeneous interest rates across countries, there is still no publicly available Divisia aggregate that takes into account the heterogeneity of the euro area. In this section, we compute a euro area wide Divisia aggregate by adopting the heterogeneous country approach of Barnett (2007).…”
Section: Datamentioning
confidence: 99%
“…Assuming that euro area countries have already converged, he applied a single euro area wide interest rate for each of the monetary assets. Darvas (2015) proposed a Divisia aggregate for the euro area under similar homogeneity assumptions. However, since the run-up to the great recession, there has been a significant degree of heterogeneity in the level of interest rates and the composition of monetary assets in the euro area.…”
Section: Introductionmentioning
confidence: 99%
“…The Divisia indices, originated from [4], apply different weights to different assets in accordance with the degree of their contribution to the flow of monetary services in an economy. The computation of the Divisia monetary aggregates for the Eurozone was conducted by [22] (the data is available at: http://bruegel.org/publications/datasets/divisia-monetary-aggregates-for-the-euro-area/).…”
Section: The Datamentioning
confidence: 99%